Pengaruh Perceived Usefulness dan E-trust terhadap Intention to Use E-wallet DANA (Studi pada Generasi Z Pengguna DANA di Kota Semarang) - Ira Gusmiarti; Naili Farida; Andi Wijayanto (Jurnal Ilmu Administrasi Bisnis, 2025)
Abstract: This research aims to determine the influence of Perceived Usefulness and E-trust on Intention to Use through Attitude toward Using of generation Z DANA users in the city of Semarang. This type of research uses explanatory research with sample size of 100 respondents who are generation Z users of DANA e-wallet in Semarang City. The sampling technique uses non-probability sampling with purposive sampling. Data analysis used path analysis with SmartPLS 4 software. The results showed that Perceived Usefulness had positive and significant effect on Attitude toward Using, E-trust had positive and significant effect on Attitude toward Using, Attitude toward Using had positive and significant effect on Intention to Use, Perceived Usefulness has negative and insignificant effect on Intention to Use, and E-trust has positive and significant effect on Intention to Use. The findings of this research also show that Perceived Usefulness and E-trust have an indirect influence on Intention to Use through Attitude toward Using. The suggestion in this research is that DANA needs to improve its security system such as two-factor authentication and end-to-end encryption so that users feel confident in continuing to use DANA. DANA needs to develop new features that can increase added value for users. Keywords: Attitude toward Using; E-trust; Intention to Use; Perceived Usefulness Abstraksi: Penelitian ini bertujuan untuk mengetahui pengaruh Perceived Usefulness dan E-trust terhadap Intention to Use melalui Attitude toward Using pengguna generasi Z di kota Semarang. Tipe penelitian menggunakan explanatory research dengan jumlah sampel sebanyak 100 responden yang merupakan generasi Z pengguna e-wallet DANA di Kota Semarang. Teknik pengambilan sampel menggunakan non probability sampling dengan purposive sampling. Analisis data menggunakan path analysis dengan bantuan software SmartPLS 4. Hasil penelitian menunjukkan bahwa Perceived Usefulness berpengaruh positif dan signifikan terhadap Attitude toward Using, E-trust berpengaruh positif dan signifikan terhadap Attitude toward Using, Attitude toward Using berpengaruh positif dan signifikan terhadap Intention to Use, Perceived Usefulness berpengaruh negatif dan tidak signifikan terhadap Intention to Use, dan E-trust berpengaruh positif dan signifikan terhadap Intention to Use. Temuan penelitian ini juga menunjukkan bahwa Perceived Usefulness dan E-trust memiliki pengaruh tidak langsung terhadap Intention to Use melalui Attitude toward Using. Saran dalam penelitian ini yaitu DANA perlu meningkatkan sistem keamanan seperti otentikasi dua factor dan enkripsi end-to-end sehingga pengguna merasa yakin untuk terus menggunakan DANA. Selain itu, DANA perlu mengembangkan fitur-fitur baru yang dapat meningkatkan nilai tambah bagi pengguna. Kata Kunci: Attitude toward Using; E-trust; Intention to Use; Perceived Usefulness.